KLF5 is involved in regulation of IFITM1, 2, and 3 genes during H5N1 virus infection in A549 cells - Wang, H-F.; Chen, L.; Luo, J.; He, H-X. (Cellular and Molecular Biology, 2016)
The interferon-induced transmembrane (IFITM) proteins usually protect cells from many virus infections by viral entry and replication. Thus, the present study aimed to identification novel regulation factors of IFITM genes. Our data showed up-regulation of IFITM1, IFITM2, and IFITM3 genes in A549 by H5N1 virus infection. However, IFITM1 was not affected, IFITM2 and IFITM3 increases expression following different concentration H5N1 virus infection in HEK293T cells. This is the first time to find differences of IFITM1 transcription in different cells with the H5N1 virus infection. Moreover, experiments showed that H5N1 virus promotes expression of KLF4 and KLF5 in both A549 and HEK293T cells, but H5N1 virus NS1, M1, NP or PB2 alone has no obvious effect on transcription of KLF5. Overexpression of KLF5 increases transcription of IFITM1, IFITM2, and IFITM3 in A549 cells, however, it does not affect transcription of IFITM1, IFITM2, and IFITM3 in HEK293T cells. In addition, results for the first time displayed that KLF4 can up-regulate expression of IFITM5 in both A549 and HEK293T cells. In conclusion, we revealed KLF5 is involved in transcription of IFITM1, 2, and 3 thus making it a potential therapeutic activator in the future to treat viral infections through promoting the innate immune response.